Protecting the integrity of e-books in the network environment: A comparative law perspective - Dien, Nguyen Ngoc; Tuyen, Nguyen Thi Ngoc (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The digital age has ushered in a remarkable transformation in accessing literature. The rise of electronic books has democratized access to a vast library of works, fostering a more vibrant and inclusive reading culture. However, this revolution in the network ecosystem has presented unforeseen challenges. One critical concern lies in safeguarding the integrity and authenticity of e-books within this dynamic online environment. This paper examines the inadequacies of the current Vietnamese legal framework in protecting the integrity of e-books. By employing a comparative legal analysis, the current paper will investigate how copyright and related rights are addressed in the legal systems of select countries worldwide. Additionally, the paper will explore the relevant provisions of international treaties regarding the right to protect the integrity of copyrighted works. This comparative and global framework will inform the development of future-oriented perspectives on e-book integrity in Vietnam. Furthermore, the paper will propose concrete amendments to Vietnamese law that aim to strengthen the protection of authors' moral rights, particularly the right to safeguard the integrity of their works in the digital realm. These proposals aim to contribute to a broader discussion on legislative reform in Vietnam, ensuring that its legal framework effectively addresses the unique challenges posed by e-books in the digital age.